O corpo como matriz pedagógica - Solano, Lorrainy da Cruz (2010)
The contemporary conjuncture based on the capitalistic knowledge converges to the corporal consciousness that makes us see, feel, taste and hear, be in/to pieces. Disembodied reason legitimate and legislate ways of being and living socially and its development is the dehumanization of human relations causing pain and suffering. The objective of this work is to discuss the body as pedagogical matrix through imagistic/artistic elements: music, painting and literature. Metaphors lead to self knowledge of human subjectivity and approach us to the kaleidoscope of sensitive knowledge and enables learning to learn with the infinite combinations of images, knowledge, feelings and worldviews. The song Memória da Pele comes in the voice of Maria Betânia speak of the memories that are not mine, but are tattooed in me in the memory of skin, singing the memories of a love lived by who tries to forget rationally, but the body insists on remembering. It is password to think about what we are. The short story by Clarice Lispector, entitled Miss Algarve, narrates the life story of an unmarried and virgin woman, and her encounter with an alien called Ixtlan. Until then, she who lived as if every day were a Monday, found herself seduced by the pleasure of having a body in contact with another body, which also allowed her to give visibility to the bodies of others. She had repudiation by the immorality that her body and the other s perspired. The discovery of the body brings important lessons for nursing, involving our body and the others'. The painting the flying bed or Henry Ford Hospital, by Frida Kahlo, is our final metaphor. The traumatic experience of abortion is shown in this painting trough the picture of the artist naked in a hospital bed. This painting invites us to reflect on our work process. We need to think in multiple dimensions of the being and accept the invitation of art, so that the lightness confronts us with the weight imposed by the hegemonic ideology. I believe it is not a single view, but the many views that should justify the knowledge and practices of nursing; what matters is that they are woven into the dialogue, democracy, provided that protagonism of those individuals involved in this process, in the wandering and uncertainty, in the rewiring, solidarity, plurality. To this end, the body must be the great pedagogue that is able to be viewed not as a tapestry seen by the right view, as the logical knowledge sees, but seen by the opposite side in its singular, irregular, discontinuous weavings